Relationship Between Knowledge Level And Behavior Of Disposing Damaged And Expired Medicine In The Community Of Marga Mulia Village, Kutai Timur Regency - Sinaga, Clara Ritawany; Elvinda, Esty; Annafiatuzakiah (PHARMACON, 2025)
Damaged or expired drugs are drugs conditions whose concentration has been reduced between 25-30% of the initial concentration and physical forms that have changed, drugs whose form or condition can no longer be used. Errors in the disposal of leftover drugs, damaged drugs and expired drugs in the household can result in an increase in drugs waste that can harm the environment and health. The purpose of this study is to determine the level of community knowledge, the description of community behavior and the relationship of knowledge level to the behavior of disposal of damaged and expired drugs in the community of Marga Mulia Village, East Kutai Regency. This study used a quantitative descriptive design, sampling was carried out using a non-probability sampling method with a purposive sampling approach and data collection using questionnaire involving 100 respondents. Based on the results of data analysis, it shows that the level of public knowledge is included in the poor category (36%). Meanwhile, after education, it shows that the level of public knowledge is included in the good category (89%). Depictions of behavior before education with positive (48%) and negative (42%) categories. While post-education behavior with positive (51%) and negative (49%) categories. The results of the analysis using the chi square test before education obtained a value (p = 0.019) which showed that there was a relationship between knowledge of damaged and expired drugs disposal behavior in the community. Meanwhile, after education, a value (p = 0.803) was obtained which showed that there was no relationship between knowledge of damaged and expired drugs disposal behavior in Marga Mulia Village, Kutai Timur Regency.